2002
DOI: 10.1046/j.1365-2168.2002.01981.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of immunohistochemical nodal micrometastasis as a prognostic indicator in potentially curable oesophageal carcinoma

Abstract: Background: The number of positive lymph nodes is an important prognostic predictor in patients with oesophageal cancer. However, the signi®cance of nodal micrometastasis in patients with overt nodal metastasis is unknown. The aim of this study was to clarify the clinical implications of nodal micrometastasis in patients undergoing curative oesophagectomy for oesophageal cancer.Methods: Cervical, mediastinal and abdominal lymph nodes systematically removed from 104 patients with oesophageal cancer were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 22 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…There is a strong body of evidence suggesting that immunohistochemically detected micrometastatic deposits in oesophageal cancer are associated with reduced survival and increased risk of disease recurrence [55][56][57][58][59][60][61][62][63][64][65]. Several studies have identified micrometastatic spread to be an independent prognostic indicator in oesophageal adenocarcinoma [35,39,41,43,66] and it has been postulated that these micrometastatic deposits may help to explain why up to 50% of histologically nodenegative oesophageal cancer patients develop recurrence, despite a curative resection of the primary tumour [67,68].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…There is a strong body of evidence suggesting that immunohistochemically detected micrometastatic deposits in oesophageal cancer are associated with reduced survival and increased risk of disease recurrence [55][56][57][58][59][60][61][62][63][64][65]. Several studies have identified micrometastatic spread to be an independent prognostic indicator in oesophageal adenocarcinoma [35,39,41,43,66] and it has been postulated that these micrometastatic deposits may help to explain why up to 50% of histologically nodenegative oesophageal cancer patients develop recurrence, despite a curative resection of the primary tumour [67,68].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Of the limited research conducted to date, Komukai, et al found that the predictive power of iNM in node-positive esophageal cancer patients varies according to the number of positive nodes, being a significant indicator of poor survival in patients with four or fewer positive nodes but not in patients with five or more. 3) Thus, the identification of a new predictor of overall survival for all patients with esophageal cancer undergoing R0 resection, regardless of whether they undergo preoperative treatment-the simultaneous presence of pNM and iNM-in the present study is significant. Specifically, simultaneous presence of pNM and iNM was found to be the only independent prognostic factor in patients who had undergone preoperative treatment, and not a factor in patients who had not undergone preoperative treatment.…”
Section: Discussionmentioning
confidence: 65%
“…3,4) Although several studies have reported that the predictive value of iNM differs among patients according to the number of pathological lymph node metastases, 3) the significance of simultaneous pNM and iNM has not been reported to date.…”
mentioning
confidence: 99%
“…[27][28][29][30] On the other hand, many reports have indicated that immunohistochemical nodal micrometastasis is a significant prognostic indicator in patients with cN0 esophageal cancer. [31][32][33] Although SN mapping in esophageal cancer is obviously more invasive than other imaging techniques, nodal micrometastasis in SN that may affect survival of the patient cannot be ignored. At present, SN biopsy is believed to detect micrometastasis more accurately and cost-effectively than other imaging procedures in patients with cN0 early esophageal cancer.…”
Section: Micrometastasis In Sentinel Nodes Of Patients With Early Esomentioning
confidence: 99%